Ketidaksantunan Berbahasa dalam Webtoon “The Secret Of Angel (True Beauty)”: Kajian Psikopragmatik - Helnisza, Vella; Revita, Ike; Aslinda, Aslinda (Faculty of Languages and Arts, Universitas Negeri Padang, 2024)
This study examines linguistic impoliteness in the webtoon “The Secret of Angel (True Beauty)” by Yaongyi through a psychopragmatic approach. The background of this research highlights the increasing use of impolite language, particularly among teenagers, on digital platforms such as webtoons. The study aims to identify categories of linguistic impoliteness, analyze indicators of impoliteness, and explore its impact on interlocutors within the story's context. A descriptive qualitative method is employed, analyzing twelve episodes out of a total of two hundred fifty-seven episodes of the webtoon. Data were collected through observation and analyzed using content analysis methods. The results indicate that there are three categories of linguistic impoliteness: face-threatening, negative face-threatening, and face-removing impoliteness. Face-threatening impoliteness is the most dominant category, followed by negative face-threatening and face-removing. In conclusion, linguistic impoliteness in this webtoon is significantly influenced by the social relationships and psychological conditions of the characters, which in turn impact readers' perspectives and attitudes toward the social issues presented in the story.